2020
DOI: 10.1175/bams-d-18-0269.1
|View full text |Cite
|
Sign up to set email alerts
|

A Global Drought and Flood Catalogue from 1950 to 2016

Abstract: Hydrological extremes, in the form of droughts and floods, have impacts on a wide range of sectors including water availability, food security, and energy production. Given continuing large impacts of droughts and floods and the expectation for significant regional changes projected in the future, there is an urgent need to provide estimates of past events and their future risk, globally. However, current estimates of hydrological extremes are not robust and accurate enough, due to lack of long-term data recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 146 publications
0
78
0
Order By: Relevance
“…This data set combines field observations from China Meteorological Administration, satellite precipitation from the Tropical Rainfall Measuring Mission (TRMM), Global Energy and Water Exchanges‐Surface Radiation Budget (GEWEX‐SRB), and the Princeton Global Forcing (X. He, Pan et al., 2020; Sheffield et al., 2006). The meteorological data used in this study include temperature, radiation, water vapor pressure, specific humidity, precipitation, and barometric pressure from 1982 to 2009.…”
Section: Study Area and Datamentioning
confidence: 99%
“…This data set combines field observations from China Meteorological Administration, satellite precipitation from the Tropical Rainfall Measuring Mission (TRMM), Global Energy and Water Exchanges‐Surface Radiation Budget (GEWEX‐SRB), and the Princeton Global Forcing (X. He, Pan et al., 2020; Sheffield et al., 2006). The meteorological data used in this study include temperature, radiation, water vapor pressure, specific humidity, precipitation, and barometric pressure from 1982 to 2009.…”
Section: Study Area and Datamentioning
confidence: 99%
“…As a consequence of global warming, hydrological fluctuation events such as excessive rainfall and droughts are common and projected to continue in the future, affecting economic activities [ 1 ]. Alterations in water availability in the field, either caused by water surplus or deficit, produce water stress in plants that negatively impacts the growth and productivity of crops worldwide [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in TWS also correspond to water mass movement between land and ocean and have recently emerged as the dominant cause of interannual variability in global mean sea level [2][3][4] . Many studies indicated that regional imbalances and extreme changes in TWS caused by human activities have been increasing, and this trend is expected to continue in the current century [5][6][7] . Under these circumstances, it is essential to properly understand the change of TWS and predict the change of TWS based on the understanding in terms of securing stable water resources for human beings and the ecosystem.…”
Section: Introductionmentioning
confidence: 99%